HLA, gut microbiome and hepatic autoimmunity - Terziroli Beretta-Piccoli, Benedetta; Mieli-Vergani, Giorgina; Vergani, Diego (Frontiers in Immunology, 2022)
Genetic susceptibility to autoimmune liver diseases is conferred mainly by polymorphisms of genes encoding for the human leukocyte antigens (HLA). The strongest predisposition to autoimmune hepatitis type 1 (AIH-1) is linked to the allele DRB1*03:01, possession of which is associated with earlier disease onset and more severe course. In populations where this allele is very rare, such as in Asia, and in DRB1*03-negative patients, risk of AIH-1 is conferred by DRB1*04, which is associated with later disease onset and milder phenotype. AIH type 2 (AIH-2) is associated with DRB1*07. The pediatric condition referred to as autoimmune sclerosing cholangitis (ASC), is associated with the DRB1*13 in populations of Northern European ancestry. DRB1*1501 is protective from AIH-1, AIH-2 and ASC in Northern European populations. Possession of the DRB1*08 allele is associated with an increased risk of primary biliary cholangitis (PBC) across different populations. DRB1*03:01 and B*08:01 confer susceptibility to primary sclerosing cholangitis (PSC), as well as DRB1*13 and DRB1*15 in Europe. The hepatic blood supply is largely derived from the splanchnic circulation, suggesting a pathophysiological role of the gut microbiome. AIH appears to be associated with dysbiosis, increased gut permeability, and translocation of intestinal microbial products into the circulation; molecular mimicry between microbial and host antigens may trigger an autoaggressive response in genetically-predisposed individuals. In PBC an altered enteric microbiome may affect intestinal motility, immunological function and bile secretion. Patients with PSC have a gut microbial profile different from health as well as from patients with inflammatory bowel disease without PSC.